DESAIN MANAJEMEN RISIKO BERBASIS ISO 31000 PADA PDAM TIRTA MEULABOH - Zainal Putra; Syafruddin Chan; Moenawar Iha (Universitas Teuku Umar, 2018)
Regional Water Company (PDAM) Tirta Meulaboh is the only state- ownedof West Aceh district that provides clean water for the residents of West Aceh, especially the residents of the city of Meulaboh and its surroundings. But in its operation the company has not yet to have a risk management system, so it has the impact on the company’s survival and not optimal service to its customers. The study aims to identify risk, risk analysis and risk evaluation, in order to do prevention and mitigation of the impact of risk on each section in PDAM Tirta Meulaboh using risk management system standard ISO 31000. The process steps of risk management based on ISO 31000, starting from risk identification to methods Risk Breakdown Structure (RBS), risk analysis using matrix risk quantification and Risk Priority Number (RPN), and the evaluation of risks by using risk map. The results showed that in PDAM Tirta Meulaboh there were 43 risk events that have the potential business problems, which if they were not solved immediately it could affect the performance of the company, even the survival of the company. Of the 43 potential risks that were logged to the red zone, there were 5 potential risks which occupies the first rank is on productions departement: the defective of production water meter, the defective of distribution water meter and retrieval water by tank car without through the water meter. Branch Kaway XVI: customers are reluctant to pay the water bill and in IKK Rantau Panjang: water meter of raw water was damaged. The Efforts to mitigate against the risk of those 43 events which were logged in the red zone has not been planned and done yet by the management of PDAM Tirta Meulaboh.Key words: ISO 31000, PDAM Tirta Meulaboh, Risk Management.